1969
DOI: 10.1111/j.1423-0410.1969.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Serological Study on the Prediction and Diagnosis of ABO Haemolytic Disease of the Newborn (ABO HD)

Abstract: Summary. An evaluation is given of haemolysin, neutralisation, thermostability, saline titration, anti‐Ap antibody absorption and 2‐mercapto‐ethanol studies on the sera from 178 clinically affected ABO HD cases and 130 control cases. The antiglobulin titre on the 2‐mercapto‐ethanol treated sera which determines the IgG titre was the best procedure used for the demonstration of significant immune anti‐A/B antibodies in the maternal sera. The screen series on 5,704 sera from group 0 mothers for the detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 49 publications
4
46
0
1
Order By: Relevance
“…23 Bowley and Voak had identified that eluate from the infant's red cells with weak positive or negative DAT might give strong indirect antiglobulin reactions with adult A1 red cells, because elution causes increase in antibody concentration. 6,19 In our analysis, concurrent DAT and elution positivity (30.9%) were significantly associated with 4.8 times amplified risk for higher bilirubin levels when compared to those in which antibody was detected only by elution (22.7%). Likewise, Dharmayani et al had observed that those with DAT and elution positivity in concert had a 3.2 times higher risk for higher bilirubin levels when compared to elution alone positive group.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…23 Bowley and Voak had identified that eluate from the infant's red cells with weak positive or negative DAT might give strong indirect antiglobulin reactions with adult A1 red cells, because elution causes increase in antibody concentration. 6,19 In our analysis, concurrent DAT and elution positivity (30.9%) were significantly associated with 4.8 times amplified risk for higher bilirubin levels when compared to those in which antibody was detected only by elution (22.7%). Likewise, Dharmayani et al had observed that those with DAT and elution positivity in concert had a 3.2 times higher risk for higher bilirubin levels when compared to elution alone positive group.…”
Section: Discussionmentioning
confidence: 53%
“…5 Bowley and Voak suggested that an IgG titre of ≥ 256 in maternal serum had provided a good presumptive evidence of ABO HDFN. 6 In India, Gupte and Bhatia noticed that all cases of ABO HDFN showed a raised incomplete antibody titre ranging from 1:16 -1:32. In our investigation, mothers of two severely affected infants with ABO HDFN had a very high titre of antibodies (1024).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency of ABO-HDFN was 0.8% in that study. 29 Murray et al observed that the frequency of HDFN triggered by anti-A was about 1 in 150 births and even lesser for anti-B. 30 The relative frequency of ABO-HDFN varied in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Sephadex separation of IgM anti-A from IgG anti-A: DEAE Sephadex A-50 was used, and the preparation of the gel and the method employed was that of Webb [12]. The techniques used in the estimation of ABH substance in serum, the thermostability test and the use of 2-mercaptoethanol were those of Voak and Bowley [10]. The partial neutralisation test was that described by Dunsford and Bowley [2],…”
Section: Introductionmentioning
confidence: 99%